EFEKTIVITAS PEMBERIAN PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN MEDIA KALENDER DALAM MENINGKATKAN PENGETAHUAN IBU DALAM MENDETEKSI DINI PNEUMONIA PADA BALITA DI DESA SECANGGANG KAB.LANGKAT - Mira Indrayani; Khairani; Rahmawani Fauza (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
Pneumonia is one of the most serious infectious diseases in children and is one of the most common acute respiratory infections (ARI) which causes death in children under five. Pneumonia is a major cause of morbidity and mortality in children under five. Every year more than 2 million children in the world die from pneumonia and most (99%) occur in developing and least developed countries. The purpose of this study was to determine the effectiveness of providing health education using calendar media in increasing mother's knowledge in early detection of pneumonia in children under five in Secanggang Village, Kab. Langkat. This type of research uses a quasi-experimental research design with